FILSAFAT AKHLAK PERSFEKTIF IBNU MISKAWAIH - Elhayat, Syarifuddin (Fakultas Agama Islam, 2019)
Ibn Miskawaih is one of the most philosophical Muslims who reviews and refutes morals. According to Miskawaih, there are times when humans change their morals so that the rules of shari'a, deliberation, and rules of tradition are needed in accordance with courtesy. Ibnu Maskawaih also paid attention to the process of moral education in children. In his view, children's psyche is like the link of animal spirit with intelligent human soul. According to him, the end of the child's soul ends animal and human horizon begins. Therefore, children must be educated with noble character. The problem of Ibn Maskawaih's study of morals is al-Khair (kindness), as-Sa'adah (happiness) and al-Fadhilah (virtue). According to Miskawaih excellence is a state where we reach the final limit of the perfection of existence. According to him the highest happiness is freedom which brings together two aspects; Aspects related to always thinking about the nature of existence and practical aspects consisting of the virtues of the soul that produce good behavior. In my journey, the highest happiness achieved by humans always adheres to the values of the Shari'a, as a guide for their path.